An annotated list of the species of Gangesia Woodland, 1924 (Cestoda: Proteocephalidea), parasites of catfishes in Asia, with new synonyms and a key to their identification - Ash, Anirban; de Chambrier, Alain; Shimazu, Takeshi; Ermolenko, Alexey; Scholz, Tomáš (Systematic parasitology, 2015)
An annotated list of tapeworms of the genus Gangesia Woodland, 1924 (Cestoda: Proteocephalidea), parasites of siluriform fishes in Asia, is provided. Based on the morphological examination of museum specimens and newly collected material from China, Japan and Russia, as well as the results of a previous revision of the Indomalayan species, only eight of more than 50 nominal taxa are considered to be valid. These are: from India and neighbouring countries, Gangesia bengalensis (Southwell, 1913) (type-species), G. agraensis Verma, 1928, both from Wallago attu (Bloch & Schneider) (Siluridae), G. macrones Woodland, 1924 from Sperata seenghala (Sykes) (Bagridae) and G. vachai (Gupta & Parmar, 1988) from different catfishes (type-host Eutropiichthys vacha (Hamilton); Schilbeidae), and, from the Palaearctic, G. margolisi Shimazu, 1994, a parasite of Silurus biwaensis (Tomoda) (Siluridae) in Japan, G. oligonchis Roitman & Freze, 1964 from Tachysurus fulvidraco (Richardson) (Bagridae) in Russia, and G. parasiluri Yamaguti, 1934 and G. polyonchis Roitman & Freze, 1964, both from Silurus asotus L. (Siluridae) in Japan and Russia, respectively. The poorly known G. oligonchis is redescribed. Seven new synonyms are proposed: G. chauhani Mathur & Srivastav, 2000, G. wallaguae Pradhan, Kulkarni, Kale & Wakle, 2010 and G. shivajiraoi Dhole, Waghmare & Chavan, 2012 are synonymised with G. agraensis; G. striatusii Bhure & Nanaware, 2012 and Silurotaenia govindii Sawarkar, 2013 with G. macrones; G. spasskajae Demshin, 1987 with G. polyonchis; and Silurotaenia spinula Chen, 1984 with Postgangesia orientalis Akhmerov, 1969. Gangesia pseudobagrae Chen, 1962 is considered to be a species inquirenda, whereas G. chauhani Mathur, 1992 and G. dineshei Jaysingpure, 2002 are recognised as unavailable names. An amended generic diagnosis of Gangesia and a key to the identification of its recognised species are also provided.
Keywords: Cestoda; Asia; Catfishes; druhová specificita; Animals; Asie; sumci; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; zvířata; Species Specificity